1993
DOI: 10.1152/ajpregu.1993.265.4.r772
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pregnancy on the response to the TxA2/PGH2 analogue U-46619 in rabbits

Abstract: We compared the hemodynamic actions of U-46619, a stable thromboxane A2 (TxA2) prostaglandin H2 (PGH2) analogue, in nonpregnant (NP) rabbits with those observed in late pregnant (P) rabbits. An intravenous injection of U-46619 (10 micrograms) to each of eight NP chronically instrumented rabbits (mean body weight 3.4 kg) induced an immediate (1 min) and reversible fall of cardiac output (CO, 66%) and mean arterial pressure (MAP, 41%, both P < 0.01). P rabbits (n = 6, mean body weight 3.8 kg), however, responded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…kg measured in both P and NP rabbits of the present study. Further, TPRI was proportionately higher by about 70%, in both P and NP rabbits, under anaesthesia than in conscious P and NP rabbits (Losonczy et al, 1993;1995). Thus, anaesthesia and surgery do not seem to influence differentially baseline haemodynamics in NP and P rabbits and the pregnancy-induced falls in MAP and TPR were well maintained.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…kg measured in both P and NP rabbits of the present study. Further, TPRI was proportionately higher by about 70%, in both P and NP rabbits, under anaesthesia than in conscious P and NP rabbits (Losonczy et al, 1993;1995). Thus, anaesthesia and surgery do not seem to influence differentially baseline haemodynamics in NP and P rabbits and the pregnancy-induced falls in MAP and TPR were well maintained.…”
Section: Discussionmentioning
confidence: 85%
“…However, in conscious, chronicallyinstrumented rabbits COI was around 200 ml min-'. kg in both P and NP animals (Losonczy et al, 1993;1995) Gy. Losonczy et at Nhric oxide and blood pressure in rabbit pregnancy compared to the value of 150 ml min .…”
Section: Discussionmentioning
confidence: 91%
“…These effects were independent of angiotensin II whereas cyclooxygenase inhibition and thromboxane A2/prostaglandin H2 receptor blockade prevented the pressor response to reductions in uteroplacental perfusion pressure. 16 Later studies in pregnant rabbits [17][18][19] and rats, 20 showed that agonists of the thromboxane A2/prostaglandin H2 receptors are more potent hypertensive substances than in nonpregnant controls, a finding that, together with that of Woods, 16 supports a role for thromboxane A2 as a potential mediator of preeclamptic hypertension. Abitol et al also observed marked increases of BP in conscious dogs in response to chronic uteroplacental ischemia, 21 although BP was very variable in controls.…”
Section: The Uteroplacental Ischemia Model Of Preeclampsiamentioning
confidence: 94%
“…CONSCIOUS, CHRONICALLY INSTRUMENTED RABBITS: The protocol followed was described previously in similar studies (10,19,20). After induction of general anesthesia, the left femoral artery was isolated and catheterized so that the catheter tip lay in the distal aorta.…”
Section: Physiological Studiesmentioning
confidence: 99%
“…All experiments were undertaken in a quiet room. MAP and HR were measured using the Cardiomax II System (Columbus Instruments) via the arterial line (10,19,20).…”
Section: Physiological Studiesmentioning
confidence: 99%